Changing the Canvas of Business Value Proposals in the Context of Achieving Sustainable Development Goals - Polinkevych, Oksana; Khovrak, Inna; Trynchuk, Viktor (<center>Conference Proceedings Determinants Of Regional Development</center>, 2022)
The article highlights the issue of changing the canvas of business value proposals to ensure sustainable development under the influence of the armed conflict in the East, the Covid-19 pandemic and the war by the aggressor. The research methodology is based on a review of the literature, a survey and a qualitative case study. The obtained results allow to identify the vector of changes in business value proposals under the influence of conflicts and pandemics, as well as to propose an approach for adapting business to changes caused by crises, pandemics and armed conflicts.